Searching for the FED's reaction function - Katrin Woelfel; Christoph S. Weber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
There is still some doubt about those economic variables that really matter for the FED's decisions. In comparison to other estimations, this study uses the approach of Bayesian Model Averaging (BMA). The estimations show that over the long run inflation, unemployment rates, and long-term interest rates are the crucial variables in explaining the Federal Funds Rate. In the other two estimation samples, also the federal deficit and M2 were of relevance. In addition, we present the best models in more detail. Finally, a model average is constructed via BMA. The model average substantially outperforms a simple Taylor rule.
Keywords: E43; E52; E58; 330; FED; Monetary Policy Reaction Functions; Model Uncertainty; Bayesian Model Averaging